Case Report: Training Monitoring and Performance Development of a Triathlete With Spinal Cord Injury and Chronic Myeloid Leukemia During a Paralympic Cycle - Quittmann, Oliver J.; Lenatz, Benjamin; Bartsch, Patrick; Lenatz, Frauke; Foitschik, Tina; Abel, Thomas (Frontiers in Rehabilitation Sciences, 2022)
Introduction: Paratriathlon allows competition for athletes with various physical impairments. The wheelchair category stands out from other paratriathlon categories, since competing in swimming, handcycling and wheelchair racing entails substantial demands on the upper-extremity. Hence, knowledge about exercise testing and training is needed to improve performance and avoid overuse injuries. We describe the training monitoring and performance development throughout a Paralympic cycle of an elite triathlete with spinal cord injury (SCI) and recent diagnosis of chronic myeloid leukemia (CML). Case Presentation/Methods: A 30-year-old wheelchair athlete with ten-year experience in wheelchair basketball contacted us for guidance regarding testing and training in paratriathlon. Laboratory and field tests were modified from protocols used for testing non-disabled athletes to examine his physical abilities. In handcycling, incremental tests were used to monitor performance development by means of lactate threshold (POBLA) and define heart rate-based training zones. All-out sprint tests were applied to calculate maximal lactate accumulation rate (V̇Lamax) as a measure of glycolytic capabilities in all disciplines. From 2017 to 2020, training was monitored to quantify training load (TL) and intensity distribution (TID). Results: From 2016 to 2019, the athlete was ranked within the top ten at European and World Championships. From 2017 to 2019, annual TL increased from 414 to 604 h and demonstrated a shift in TID from 77-17-6% to 88-8-4%. In this period, POBLA increased from 101 to 158 W and V̇Lamax decreased from 0.56 to 0.36 mmol·l-1·s-1. TL was highest during training camps. In 2020, after he received CML-diagnosis, TL, TID and POBLA were 317 h, 94-5-1%, and 108 W, respectively. Discussion: TL and TID demonstrated similar values when compared to previous studies in para swimming and long-distance paratriathlon, respectively. In contrast, relative TL during training camps exceeded those described in the literature and were accompanied by physical stress. Increased volumes at low-intensity are assumed to increase POBLA and decrease V̇Lamax over time. CML treatment and side-effects drastically decreased TL, intensity and performance which ultimately hindered a qualification for Tokyo 2020/21. In conclusion, there is need for careful training prescription and monitoring in wheelchair triathletes to improve performance and avoid non-functional overreaching.